Analysis of unmanned aircraft systems application in the civil field - Kharchenko, Volodymyr; Prusov, Dmitry (Transport, 2012)
The basic directions of unmanned aircraft systems applications in the civil field has been reviewed, the concepts of creation and organization of civil unmanned aircraft systems has been considered depending on the task orientation as well as the wide range of issues concerning the use of existing capacity for the design, manufacture and operation, with subsequent integration into the common air space.First Published Online: 19 Sep 2012